2014
DOI: 10.1371/journal.pone.0101731
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Lung Cancer Patients Refusing Treatment and Their Survival: A National Cohort Study under a Universal Health Insurance in Taiwan

Abstract: BackgroundLung cancer is the leading cause mortality among all cancers in Taiwan. Although Taiwan offers National Health Insurance (NHI), occasionally, patients refuse treatment. This study examined the patient characteristics and factors associated with lung cancer patients refusing cancer treatment in four months after cancer diagnosed and compared the survival differences between treated and non-treated patients.MethodsThe study included 38584 newly diagnosed lung cancer patients between 2004 and 2008, coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 32 publications
6
36
3
Order By: Relevance
“…Older age (poor physical condition) and difficulty in enduring any condition likely to cause physical discomfort from the disease treatment were also reasons for refusing treatment. This is consistent with previous studies that found old age was a common reason for refusing treatment (Chen et al., ; Choi et al., ; Huang et al., ). More than one‐third of patients in the case group who refused treatment were more than 80 years of age and most were diagnosed with stage III or IV CRC.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Older age (poor physical condition) and difficulty in enduring any condition likely to cause physical discomfort from the disease treatment were also reasons for refusing treatment. This is consistent with previous studies that found old age was a common reason for refusing treatment (Chen et al., ; Choi et al., ; Huang et al., ). More than one‐third of patients in the case group who refused treatment were more than 80 years of age and most were diagnosed with stage III or IV CRC.…”
Section: Discussionsupporting
confidence: 93%
“…This study of CRCs patients found that a total of 68 patients refused treatment. In our study, patients with CRC had a lower rate of refusal than those in previous studies (El Shayeb et al., ; Huang et al., ) and at the study institute prior to case management. This finding may be explained by the fact that over half of our study participants were at an early cancer stage at initial diagnosis than participants studied elsewhere.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Refusal of cancer treatment might result in rapid deterioration, emergence of physical symptoms, and metastasis. A study conducted in Taiwan showed that the mortality risk for lung cancer patients refusing treatment was elevated 2.1‐fold . Other studies of breast and colorectal cancer have consistently revealed that patients who delayed or refused therapy had lower five‐year survival rates compared to treated patients .…”
Section: Introductionmentioning
confidence: 99%
“…[4] Seeking a second opinion may also cause patients to delay treatment. [5] In Taiwan, a study by Huang et al [6] showed lung cancer patients who had higher treatment refusal rates were associated with factors such as men, older adults, high prediagnosis Charlson comorbidity index (CCI) score, other catastrophic illnesses or injury, and advanced cancer stage. The National Health Insurance (NHI) Program covers 99.9% of the population and waives copayments for patients with cancer.…”
Section: Introductionmentioning
confidence: 99%